BUILDING VISION AND VOICE BASED ROBOTS USING ANDROID - Pradeep N.; Mohammed Sharief; M. Siddappa (European Scientific Journal, ESJ, 2013)
This project uses Android, along with cloud based APIs and the Arduino microcontroller, to create a software-hardware system that attempts to address several current problems in robotics, including, among other things, line-following, obstacle-avoidance, voice control, voice synthesis, remote surveillance, motion & obstacle detection, face detection, remote live image streaming and remote photography in panorama & time-lapse mode. The rover, built upon a portable five-layered architecture, will use several mature and a few experimental algorithms in AI, Computer Vision, Robot Kinetics and Dynamics behind-the-scene to provide its prospective user in defense, entertainment or industrial sector a positive user experience. A minimal amount of security is achieved via. a handshake using MD5, SHA1 and AES. It even has a Twitter account for autonomous social networking.